Ephyrina benedicti S.I.Smith 1885 - Cardoso, Irene; Contents, Paulo Young Table Of (Zenodo, 2005)
Ephyrina benedicti Smith, 1885 (Figs 24–28) Ephyrina benedicti Smith, 1885: 506; De Man, 1920: 46; Crosnier & Forest, 1973: 65, figs 18, 19a; Chace, 1986: 33. Tropiocaris planipes Bate, 1888: 835, pl. 136, fig. 1. Material examined: Revizee Program: E0519, 13°19'S, 38°19'W, 1730m, 1 ovigerous female (30mm), MNRJ 14885; E0538, 20°27'S, 39°38'W, 1680m, 1 female (28mm), MNRJ 18883; E0526, 20°06'S, 38°40'W, 1637m, 1 female (30mm), 1 male (37mm), MNRJ 18884. Diagnosis: Carapace with rostrum short reaching 1/4 of scaphocerite length, unarmed; antennal and branchiostegal spine present, but not prominent; branchiostegal spine without distinct carina. Abdomen not dorsally carinate on all somites; somites 3 and 4 with posteromesial tooth, the one of somite 3 distinctly strong. Male pleopod 1, endopod rounded, posterior margin with densely plumose setae, anterior margin with a slender and elongate lobe, with stout setae on anterior margin and numerous hook setae on apex; male pleopod 2 with appendix interna, as long as appendix masculina, distal portion slightly triangular in shape, with hook setae; appendix masculina with acute simple setae on distal margin. Description: Eyestalk without an ocellus on mediodistal portion (Fig. 24B). Carapace with rostrum laterally compressed in subtriangular shape, short, reaching 1/4 of scaphocerite length, unarmed (Fig. 24A); dorsal margin not carinate; antennal and branchiostegal spines present; branchiostegal spine without distinct carina; supraorbital and pterygostomian spines absent; sinuous lateral gastroorbital carina extending from near orbit to near posterior margin; well marked cervical groove; suprabranchial carina absent (Fig. 24A). Stylocerite with straight margins, acute apex reaching end of first antennular peduncle article; first antennular peduncle article with distal margin serrate on outer half (Fig. 24C). Scaphocerite broad at base, narrowing on tip, densely plumose setae on inner margin, distal tooth on outer margin (Fig. 24D). Mandible with palp threearticulated; incisor process with about six teeth; molar process triangular, numerous small simple setae on apex (Fig. 25A, B). Maxilla 1 with two endites; distal endite with numerous stout setae on inner margin; basal endite with long, stout, pectinate setae and short, broad, plumose setae on inner margin; palp with several pappose setae on rounded apex, without protuberance (Fig. 25C). Maxilla 2 with two endites; distal endite bilobed, both lobes with long, stout, pectinate setae on inner margin; basal endite rounded, densely plumose setae on inner margin; endopod as long as endites, pappose setae on apex, several simple setae on inner margin; scaphognathite with densely plumose setae on all margins (Fig. 25D). Maxilliped 1 endite with pectinate and pappose setae on inner margin; endopod threearticulated, as long as endite, with pappose setae on apex, several simple setae on inner margin; exopodal lobe with densely plumose setae in all margins (Fig. 25E). Maxilliped 2 endopod with elongate ischium and merus, pappose setae on inner margin; carpus short; propod rounded with pectinate and long, stout, pectinate setae on inner margin; dactyl with long, stout setae on inner margin, and several long, stout, pectinate setae on distal margin; exopod with densely plumose setae on all margins (Fig. 25F). Maxilliped 3 slender and elongate, propoddactyl with stout setae on apex; exopod with densely plumose setae on all margins (Fig. 25G). Pereopods 1 and 2 not chelate, dactyl with many stout setae. Pereopods 3 to 5 with ischium and merus laterally strongly compressed. Pereopod 3, merus with five stout setae on inner margin. Pereopod 4, merus with four stout setae on inner margin. Pereopod 5, merus with three stout setae on inner margin (Fig. 24A). Epipods with mesial teeth, on pereopods 1 to 3 (Fig. 26A, B). Abdomen without dorsal carina on somites; somites 3 and 4 with posteromesial tooth; the one of somite 3 distinctly strong; somite 6 at least 1 ½ times longer than high (Fig. 24A). Male pleopod 1 endopod rounded, densely plumose and stout setae on posterior margin, distal lobe slender and elongate with stout setae on anterior margin and numerous hook setae on apex (Fig. 26C); Male pleopod 2 with long, slender, appendix masculina acute simple setae on apex; appendix interna as long as appendix masculina, apex slightly triangular, numerous hook setae (Fig. 26D). Female pleopod 1 endopod rounded, densely plumose setae on all margins (Fig. 26E). Exopod of uropod with complete diaresis, one distal spine on outer margin (Fig. 27). Telson not sulcate in dorsal midline, with about 24 pairs of dorsolateral stout setae, without distal setae (Fig. 27). Distribution: Western Atlantic: South Greenland (56°56'S; 51°17'W), U.S.A. (40°26'S; 67°05'W), Brazil (Bahia, Espírito Santo). Eastern Atlantic: southwest Ireland (50°28'S; 11°39'W), west Portugal (36° to 45°S; 11°W), west Canary Archipelago, Gabon, Saint Tomé Island. Indian and Pacific Oceans: northeastern Philippine Sea, west of Bonin Islands, Japan, Hawaii. Adults probably are mesopelagic and bathypelagic (Crosnier & Forest 1967; Chace 1986; Crosnier 1987). Remarks: This species occurs on Indian, Pacific and Atlantic Oceans. In the Western Atlantic this species was recorded only from North America. This is the first record of this genus and species from Brazilian waters (South America) (Fig. 28). Ephyrina emcompasses six species, four of them occurring in the North Western Atlantic. Of these, two ( E. figueirai Crosnier & Forest, 1973 and E. ombango Crosnier & Forest, 1973) have abdominal somite 3 without a dorsal tooth, distinct from E. benedicti and E. bifida Stephensen, 1923 that have abdominal somite 3 with a dorsal tooth. Ephyrina bifida has abdominal somite 3 with bifid dorsal tooth, and the telson with four to seven pairs of dorsolateral stout setae, while E. benedicti has abdominal somite 3 with a simple dorsal tooth, and the telson with 22 to 27 pairs of dorsolateral stout setae. The samples examined herein agree with the description of Smith (1885) in the carapace and abdominal somites without a dorsal carina, the simple dorsal tooth on abdominal somite 3 and the telson much longer than the sixth somite, with 20 to 25 dorsolateral stout setae. Crosnier & Forest (1973) illustrated the suprabranchial carina but not the cervical groove observed in the present material. : Published as part of Cardoso, Irene & Contents, Paulo Young Table Of, 2005, Deep-sea Oplophoridae (Crustacea Caridea) from the southwestern Brazil, pp. 1-76 in Zootaxa 1031 (1) on pages 33-39, DOI: 10.11646/zootaxa.1031.1.1, http://zenodo.org/record/5050357 : {"references": ["Smith, S. L. (1885) On some new or little known Decapod Crustacea, from recent fish commission dredgings off the East Coast of the United States. Proceedings of the United States National Museum 7: 493 - 511.", "Crosnier, A. & Forest, J. (1973) Les crevettes profondes de l'Atlantique oriental tropical. Faune Tropicale, 19, 1 - 409.", "Chace, F. A. (1986) The Caridean shrimps (Crustacea: Decapoda) of the Albatross Philippine Expedition, 1907 - 1910, part 4: families Oplophoridae and Nematocarcinidae. Smithsonian Contributions to Zoology, 432, 1 - 82.", "Bate, C. S. (1888) Report on the Crustacea Macrura collected by the Challenger during the years 1873 - 76. Report on the Scientific Results of the Voyage of H. M. S. \" Challenger \" during the years 1873 - 76, 24, 1 - 942.", "Crosnier, A. & Forest, J. (1967) Note preliminaire sur les carides recueillis par l'Ombango au large du plateau continental, du Gabon a l'Angola (Crustacea Decapoda Natantia). Bulletin du Museum national d'Histoire naturelle, Paris, ser. 2, 39 (6), 1123 - 1147.", "Crosnier, A. (1987) Systellaspis intermedia (Crustacea Decapoda Oplophoridae), espece nouvelle de l'Indo- Pacifique. Bulletin du Museum national d'Histoire naturelle, Paris, ser. 4, 9 (4): 947 - 959."]}